Rethinking electronic journals : exploring the flexibility and duality of technology - Gomes, Suely (2004)
This study analyses the appropriation process of electronic journals by academics at three Brazilian post graduation research programs (Master and Doctoral). The objective is to understand the internal structure of technological practices in the context of potential users, exploring two main characteristics of the appropriation process: the duality and the flexibility of technology. The technological structuring model, proposed by Orlikowsky was expanded to verify the relationship between electronic journals and scientific communities. Results reveal electronic journals as both product of and medium for human action. As a product, technology only comes into existence through creative human action. It has no meaning until given meaning through manipulation; as a medium, technology promotes certain types of work and constrains others (duality). When interacting with electronic journals, academics showed to be influenced by the institutional properties of their setting. They based their action on existing stocks of knowledge and resources and norms to perform their work. As such, electronic journals are products of the organisational context, and will reflect the knowledge, materials, interest, and conditions present at a given locus. Electronic journals are flexible in the sense that they allow more than one interpretation. i.e., their concept vary according to the individual conditions of interaction.